Identification of a Homozygous Single Base Pair Deletion in the Gene Coding for the Human Platelet Glycoprotein Ibα Causing Bernard-Soulier Syndrome - Simsek, S; Admiraal, L G; Modderman, P W; van der Schoot, C E; von dem Borne, A E G Kr (Thrombosis and Haemostasis, 1994)
Bernard-Soulier Syndrome (BSS) is a hereditary bleeding disorder which is caused by the absence or the dysfunction of the platelet glycoprotein Ib/IX/V (GP Ib/IX/V) complex, the major receptor for von Willebrand factor (vWf). BSS is characterized by the presence of giant platelets that show a reduced binding of vWf. Although BSS is a well-characterized disease, and many cases have been described in the literature, the molecular genetic basis of this disorder has been studied in only a few patients.We have studied the genetic basis of the defect in a BSS patient. Flow cytometric analysis of the platelet membrane glycoproteins revealed a significant decrease or absence of GP Ibα on the platelet surface, and low levels of GP V and GP IX. In subsequent immunopre-cipitation experiments, we confirmed the presence of GP V (although in significantly decreased amounts) on the platelet surface. These results indicated a defect in the GP Ibα chainGenomic DNA coding for GP Ibα was amplified, using the polymerase chain reaction (PCR). Subsequent direct sequence analysis demonstrated a homozygous deletion of T317 resulting in a frameshift deletion and predicting a substitution of Arg for Leu76. This deletion causes a shift in the reading frame, predicting a premature stop codon after 19 altered amino-acids, leading to a severily truncated molecule. The molecular genetic defect found in this patient differed from the mutations observed in three other BSS patients described in the literature. This points to a marked hetereogeneity of this disease.The single basepair deletion created a target site for the restriction enzyme Hhal. This allowed us to perform PCR-ASRA (Allele-Specific Restriction enzyme Analysis) on all available family members. Both parents and the daughter of the patient appeared to be heterozygous for the deletion, while the homozygosity of the propositus for the mutant allele was confirmed.